PROSEDUR PENCATATAN TRANSAKSI KEUANGAN DI PT SMART TBK PADANG HALABAN DAN RELEVANSINYA DENGAN AKUNTANSI SYARIAH - Elvina Damayanti Br. Harahap; Muhammad Syahbudi (LPPM Politeknik Pratama, 2024)
This internship report aims to identify and analyze the financial transaction recording procedures implemented at PT SMART Tbk Padang Halaban and to assess their relevance to Sharia accounting principles. The internship was conducted for one month, from January 16 to February 16, 2023, in the Checkroll Clerk Division, which handles labor administration and operational financial recording.The research methods used include direct observation, interviews with company staff, and documentation of financial recording activities. The findings indicate that PT SMART Tbk has implemented an Enterprise Resource Planning (ERP) system using the SAP platform, enabling a more systematic, accurate, and efficient process of financial transaction recording. However, some administrative tasks are still performed manually using Microsoft Excel, which may lead to delays and potential human errors. In general, the company’s recording procedures comply with conventional accounting principles such as objectivity, reliability, and measurability. Nevertheless, from the perspective of Sharia accounting, the system has not fully reflected Islamic values such as justice (‘adl), honesty (sidq), transparency (amanah), and the avoidance of riba (usury), gharar (uncertainty), and maysir (speculation). Therefore, this report recommends that the company begin integrating Sharia accounting principles into its financial recording system through human resource training, the adjustment of Standard Operating Procedures (SOPs), and the development of Sharia-compliant modules within the ERP system. Such integration is expected to enhance the company’s ethical and spiritual accountability, ensuring that its financial reporting is not only technically reliable but also aligned with Islamic ethical values.